Congenital myasthenic syndrome with novel pathogenic variants in the COLQ gene associated with the presence of antibodies to acetylcholine receptors. (February 2020) - Tay, Chee Geap; Fong, Choong Yi; Li, Limin; Ganesan, Vigneswari; Teh, Chee Ming; Gan, Chin Seng; Thong, Meow-Keong
Highlights: COLQ-related congenital myasthenic syndrome with AChR autoantibody. COLQ-related congenital myasthenic syndrome masquerading as autoimmune myasthenia. COLQ-related CMS with heterogeneity in treatment responses. Abstract: Congenital myasthenic syndrome (CMS) is a heterogeneous group of inherited disorder which does not associate with anti-acetylcholine receptor (AChR) antibody. The presence of AChR autoantibody is pathogenic and highly sensitive and specific for autoimmune myasthenia gravis (MG). We describe 2 children from unrelated families who presented with hypotonia, ptosis and fatigability in early infancy with anti-AChR antibodies detected via ELISA on 2 separate occasions in the sera. Both were treated as refractory autoimmune MG due to poor clinical response to acetylcholinesterase inhibitor and immunotherapy. In view of the atypical clinical features, genetic studies of CMS were performed and both were confirmed to have novel pathogenic mutations in the COLQ gene. To the best of our knowledge, the presence of anti-AChR antibody in COLQ- related CMS has never been reported in the literature. The clinical presentation of early onset phenotype, and refractoriness to acetylcholinesterase inhibitor and immunotherapy should prompt CMS as a differential diagnosis.